Zinc Stannate as Anode and Pyrrolidinium-Based Room Temperature Ionic Liquid as Electrolyte for Lithium-Ion Cells - Ruiz-Leon, D; Ruiz-Leon, D (Electrochemical Science Group, 2021)
With the aim to design safer batteries, pyrrolidinium-based room temperature ionic liquids (RTIL) have been used as electrolytes in Li-ion batteries using zinc stannate as the anodic material. The lithium diffusion coefficients were calculated using Electrochemical Impedance Spectroscopy (EIS) data and were 2.37 x 10-12 cm2s-1 for MPPyrTFSI and 1.29 x 10-12 cm2s-1 for BMPyrTFSI. The performance of the device strongly depended on the cation chemical structure, yielding different specific capacity values of 306.3 mAhg-1 for BMPyrTFSI and 269.2 mAhg-1 for MPPyrTFSI. © 2021 The Authors. Published by ESG (www.electrochemsci.org). This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution license (http://creativecommons.org/licenses/by/4.0/).